2006
DOI: 10.1016/j.crhy.2005.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and superconductivity of heavy fermion matter

Abstract: The interplay of magnetism and unconventional superconductivity (d singlet wave or p triplet wave) in strongly correlated electronic system (SCES) is discussed with recent examples found in heavy fermion compounds. A short presentation is given on the formation of the heavy quasiparticle with the two sources of a local and intersite enhancement for the effective mass. Two cases of the coexistence or repulsion of antiferromagnetism and superconductivity are given with CeIn 3 and CeCoIn 5 . A spectacular example… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 79 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…In the wake of Ref. 5, numerous studies of quantum phase transitions have been reported [7][8][9][10][11][12][13][14][15][16]. Experimental studies have focused their effects on the finite temperature behavior of different physical quantities, sometimes even at unexpectedly high temperatures.…”
Section: Historymentioning
confidence: 99%
“…In the wake of Ref. 5, numerous studies of quantum phase transitions have been reported [7][8][9][10][11][12][13][14][15][16]. Experimental studies have focused their effects on the finite temperature behavior of different physical quantities, sometimes even at unexpectedly high temperatures.…”
Section: Historymentioning
confidence: 99%
“…Many unconventional superconductors feature strong magnetic fluctuations and complex ground states with either competing or coexisting magnetic and superconducting order. Because magnetic fluctuations are believed to be crucial for the formation of superconducting Cooper pairs in these materials [1,2], it is paramount to improve our understanding of how magnetism and superconductivity can interact.…”
mentioning
confidence: 99%
“…In the undoped state, three-dimensional (3D) long range ordering occurs below a Néel temperature T N of about several hundreds Kelvin [1,2], due to a small additional magnetic exchange J ′ between the layers. At the magnetic quantum phase transition of some heavy-fermion systems, the appearance of superconductivity is believed to arise from an enhancement of the magnetic fluctuations [3,4]. Hence, a better understanding of the magnetic properties of the high-T C cuprates could be of primary importance to elucidate why superconductivity develops in these systems [5].…”
Section: Introductionmentioning
confidence: 99%